High-energy O3-Na1−2xCax[Ni0.5Mn0.5]O2 cathodes for long-life sodium-ion batteries. Issue 27 (3rd July 2020) - Yu, Tae-Yeon; Kim, Jongsoon; Hwang, Jang-Yeon; Kim, Hyungsub; Han, Geumjae; Jung, Hun-Gi; Sun, Yang-Kook
Abstract : Substituting Ca for Na sites in the O3-Na[Ni0.5 Mn0.5 ]O2 cathode provides outstanding stability at high voltage where Na-ions are fully extracted. Abstract : To facilitate the practical realization of sodium-ion batteries, the energy density, determined by the output operating voltage and/or capacity, needs to be improved to the level of commercial Li-ion batteries. Herein, O3-type Na0.98 Ca0.01 [Ni0.5 Mn0.5 ]O2 is synthesized by incorporating Ca 2+ into the NaO6 octahedron of Na[Ni0.5 Mn0.5 ]O2 and its potential use as a cathode material for high energy density SIBs is demonstrated. The ionic radius of calcium (≈1.00 Å) is similar to that of sodium (≈1.02 Å); hence, it is energetically favorable for calcium to occupy sites in the sodium layers. Within a wide operating voltage range of 2.0–4.3 V, O3-type Na0.98 Ca0.01 [Ni0.5 Mn0.5 ]O2 exhibits a reversible O3–P3–O3 phase transition with small volume changes compared to Ca-free Na[Ni0.5 Mn0.5 ]O2 because of the strong interaction between Ca 2+ and O 2− and delivers a high reversible capacity of 209 mA h g −1 at 15 mA g −1 with improved cycling stability. Moreover, Ca substitution improves the practically useful aspects such as thermal and air stability. A prototype pouch full cell with a hard carbon anode shows an excellent capacity retention of 67% over 300 cycles. Thus, this study provides an efficient and simple method to boost the performance and applicability of layered oxide cathode materials for practical applications.